Slavey topical dictionary (A topical list of words and phrases reflecting the dialect of the Slavey language spoken in the Fort Simpson area) - Isaiah, Stanley; Monus, Victor P. (Victor Monus, 1977)
https://www.sil.org/resources/archives/40934